Understanding Oil Palm Smallholders’ Behavioral Intention on Sustainable Production Practices - Eko Ruddy Cahyadi; Fitri Yutika; Heti Mulyati (Jurnal Manajemen dan Organisasi, 2021)
While smallholders play a significant contribution on Indonesian oil palm production, they are confronted to sustainability challenges. This study aims to analyze determinants of their behaviour to apply sustainable practices. Theory of Planned Behavior was applied to examine the effect of attitudes, subjective norms, perceived behavioral control and past behavior toward smallholders' intention to implement sustainable oil palm production practices. In this study the sustainable practices include applying organic fertilizer, integrated pest management, non-fire land clearing, certified seed and participating in a farmer group. A survey was carried out over 242 oil palm smallholders in Kampar, Riau. Structural Equation Modeling (SEM) with Partial Least Square (PLS) program was employed to examine our hypothesis. The results show that attitudes, perceived behavioral control and past behavior have positive and significant effects on smallholders' intention to implement sustainable production practices, whereas subjective norms seems to be not significant. Smallholders tend to be individually independent in making a decision or taking action. Hence, improving attitude toward sustainability, for example, through extension service or training and providing incentives to overcome perceived behavioural control are expected to be an effective measure to encourage sustainability practices among oil palm smallholders.